Parent’s stories of the lived experience of parenting a child with Cystic Fibrosis - Downing, Hannah (2013)
Background: Cystic Fibrosis (CF) is a life-limiting chronic condition affecting over 9,000 people within the UK. Its treatment and life course has been found to render a significant burden on the individual, as well as the parents. To support parents of children with CF we need to talk to them and listen to their needs to better support them and improve their QOL; yet current studies infrequently explore parent’s experiences.